Oferta de sementes orgânicas do setor privado no Brasil - Furquim, Lucas Tadeu (Universidade Federal de São Carlos, 2021)
Given the current concern with sustainability, the organic agriculture has shown growth in recent decades, which occurred, in many cases, through common practices and technologies in conventional agriculture, especially related to seeds. The legal flexibility of allowing the use of conventional seeds in organic crops gave way to a low offer of organic seeds in the private sector, both in numbers and in species. Thus, by consulting the catalog of companies that produce organic seeds in Brazil, together with a literature review, the offer of organic seeds was analyzed, including the location of the main companies and the diversity of species. Only four companies producing organic seeds in Brazil, located in the South and Southeast regions of Brazil, except for one point of sale located in the Midwest region. All companies are focused on the production of vegetable seeds, as it is one of the largest sectors of organic agriculture, especially regarding the acquisition of seeds. However, the sector shows potential for the exploration of other cultures, and remains incipient mainly because of the difficulties in producing these seeds and the flexibility of the law.
Organic seeds offer from the private sector in Brazil
Keywords: Mercado; Convencionalização; Produção orgânica; Hortaliças; Market; Conventionalization; Organic production; Vegetables; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA